Physical and physiological demands of experienced male basketball players during a competitive game - Puente, C.; Abian-Vicen, J.; Areces, F.; Lopez, R.; Del Coso, J. (The Journal of Strength and Conditioning Research, 2017)
The aim of this investigation was to analyze the physical and physiological demands of experienced basketball players during a real and competitive game. Twenty-five well-trained basketball players (8 guards, 8 forwards, and 9 centers) played a competitive game on an outdoor court. Instantaneous running speeds, the number of body impacts above 5 g, and the number of accelerations and decelerations were assessed by means of a 15-Hz global Positioning System accelerometer unit. Individual heart rate was also recorded using heart rate monitors. As a group mean, the basketball players covered 82.6 ± 7.8 m/min during the game with a mean heart rate of 89.8 ± 4.4% of maximal heart rate. Players covered 3 ± 3% of the total distance running at above 18 km/h and performed 0.17 ± 0.13 sprints per minute. The number of body impacts was 8.2 ± 1.8 per minute of play. The running pace of forwards was higher than that of centers (86.8 ± 6.2 vs. 76.6 ± 6.0 m/min; p = 0.05). The maximal speed obtained during the game was significantly higher for guards than that for centers (24.0 ± 1.6 km/h vs. 21.3 ± 1.6 km/h; p = 0.05). Centers performed a lower number of accelerations/decelerations than guards and forwards (p = 0.05). In conclusion, the extraordinary rates of specific movements performed by these experienced basketball players indicate the high physiological demands necessary to be able to compete in this sport. The centers were the basketball players who showed lower physiological demands during a game, whereas there were no differences between guards and forwards. These results can be used by coaches to adapt basketball training programs to the specific demands of each playing position.